Combined in vivo and in silico approaches for predicting the release of bioactive peptides from meat digestion. (30th May 2018) - Sayd, T.; Dufour, C.; Chambon, C.; Buffière, C.; Remond, D.; Santé-Lhoutellier, V.
Highlights: 3 Clusters of proteins were obtained according to their dynamic of digestion. Numerous bioactive peptides from meat are potentially released in the proximal gut. The bioactivity of peptides is mainly DDP and ACE inhibition. Abstract: We studied the kinetics of peptide release during the gastric digestion of meat proteins in vivo, in view to predicting the release of bioactive peptides further on in the digestive tract. Six mini pigs fitted with gastric cannulas received a meal with cooked beef as protein source. Digesta was collected at regular time intervals up to 5½ h. The peptides generated by the gastric digestion of meat were identified and quantified using label-free LC MS, thereafter subjected to in silico digestion mimicking the action of intestinal enzymes. Three clusters of proteins presenting similar evolutions according to their dynamic hydrolysis were obtained. This study clearly improves the in silico prediction of the intestinal release of bioactive peptides by mapping meat protein degradation in the stomach in an in vivo model. Knowledge of the conformation of the peptides released in the stomach further improves this prediction.